Government's record on health services - Labour Party (Great Britain). Advisory Committee on Public Health
1927-09 1927 1920s 11 pages - 2 - The actuarial reports submitted to the Royal Commission disclosed a yearly margin of £4,700,000 in National Health Insurance funds which after providing £1,900,000 towards the cost of medical benefit, left £2,800,000 which the Royal Commission recommended could be used in one of the following ways. Either (1) in the provision of allowances in respect of dependents of insured persons in receipt of sickness or disablement benefit. Or (2) in improved provision at the time of pregnancy and child birth for insured women and the wives of insured men. Or (3) in the provision of dental treatment as a normal benefit. Had the Government adopted the recommendations of the Royal Commission and used this balance of £2,800,000 per year for any one of these benefits it would have resulted in either (a) an addition of a payment of 8/- per week to the average family during periods when the breadwinner is sick or (b) the probable reduction in the annual death-rate of 3,000 mothers whose lives are lost at childbirth, a death-rate that has been stationary for a generation, notwithstanding the reduction in infantile mortality during that period, or (c) a great improvement in the health of the insured population by making dental benefit available to all insured persons. The Government, faced with this opportunity of using this margin of £2,800,000 in one of these ways to the advantage of the health of the insured community, decided instead to reduce the State Grant to Health Insurance funds by £2¾ million per annum, thus absorbing the margin that should have been employed in one or other of the ways recommended by the Royal Commission. The action of the Government in passing the Economy Act providing for the reduction in the State Grant to Health Insurance by £2¾ million meant that they deliberately chose to relieve the income-tax payer by ½d in the £. rather than give either dependants’ allowances, better maternity services or dental benefit as a statutory right to all insured persons. 292/840/1/15